Reassessing the Validity Period of Certified Seeds in Proso Millet (Panicum miliaceum L.) - PRASHANT KUMAR RAI; SHIVAM KUMAR RAI; M LINGA SWAMI SAI REDDY; GIRASE INDRAJITSINGH PRAVINSINGH; VAIDURYA PRATAP SAHI (Seed Research, 2025)
Proso millet (Panicum miliaceum L.) is gaining renewed importance as a climate-resilient and nutritionally rich cereal capable of supporting food and nutritional security under marginal and rainfed conditions. With increasing emphasis on millet-based cropping systems, ensuring the availability of high-quality seed throughout the planting season has become critical, necessitating a re-examination of existing seed certification validity norms. The present study evaluated the storability and revalidation requirements of certified Proso millet seed varieties GPUP-25 and GPUP-28 stored under ambient conditions in cloth and high-density polyethylene (HDPE) bags for nine months. The investigation was conducted during 2024–2025 at the Notified State Seed Testing Laboratory, Department of Genetics and Plant Breeding, SHUATS, Prayagraj. Progressive declines in germination percentage, seedling dry weight and vigour indices were observed with increasing storage duration, irrespective of packaging material. However, seeds stored in HDPE bags consistently maintained superior physiological quality compared to those stored in cloth bags. By the ninth month of storage, germination in cloth bags declined below the Indian Minimum Seed Certification Standards (IMSCS) minimum of 75% (72.63%), whereas HDPE-stored seeds retained acceptable germination (83.05%). Higher moisture content and electrical conductivity values in cloth bags indicated accelerated seed deterioration. The findings demonstrate that packaging material significantly influences seed longevity and suggest that uniform certification validity periods may not adequately reflect cropand storage-specific seed behaviour. HDPE bags are recommended for medium- to long-term storage of Proso millet seeds under ambient conditions, while seeds stored in cloth bags require revalidation beyond eight months. The study provides empirical evidence to support the need for revisiting and refining seed certification and revalidation standards for Proso millet based on storability performance.